LITERATURE REVIEW ON ORGANIZATIONAL PERFORMANCE AND SUSTAINABILITY OF EDUCATIONAL NGOS FOR OBTAINING FUNDING - Siregar, Shafa Azahra; Perdhana, Mirwan Surya (Faculty of Economics and Business Diponegoro University, 2024)
ABSTRACT The primary goal of this research is to investigate and analyze the key factors that influence the performance and sustainability of non-governmental organizations (NGOs), with a specific focus on how funding may affect NGO performance and sustainability. The educational NGOs chosen for this case are Gerakan Mengajar Desa Indonesia and Mataharikecil Indonesia. This type of research uses a multi case study to provide a descriptive explanation regarding the associated challenges. The data obtained and collected was from in-depth interview and secondary data. The findings of this thesis highlight the critical elements required to improve organizational performance and ensure the sustainability of non-governmental organizations (NGOs). The study emphasizes the importance of project initialization, project results, organizational performance, and fundraising in achieving sustainability and enhancing organizational performances of non-governmental organizations. Furthermore, the study confirms that NGOs' sustainability requires a diverse range of funding and revenue streams, emphasizing the importance of financial resilience in navigating the dynamic landscape of non-profit efforts.